OPTIMALISASI ASAS KEMANFAATAN HASIL LELANG EKSEKUSI DALAM PERSPEKTIF HUKUM INVESTASI - Rusmin Wijaya; Achmad Jaka Santos Adiwijaya (Magister Hukum Sekolah Pascasarjana Unida, 2021)
The auction activity is the sale of goods open to the public with a written and / or verbal price quote that is increasing or decreasing to reach the highest price, which is preceded by an auction announcement. Auction activities can grow the country's economy, this activity can be optimized through investment. The research method used in this research is normative juridical, and the data are analyzed qualitatively using SWOT analysis. The results of this research there are opportunities and challenges where the Mortgage Certificate has an executorial power, the Regulation supports Investors / Buyers to Invest by buying auction assets, the online auction system aims to enable KPKNL to respond quickly, cheaply, efficiently every request of potential buyers / Investors without have to go through a long bureaucracy, buyers in good faith get legal protection. As for obstacles or challenges in optimizing auction results through investment, namely the presence of auction blockage before the auction, interference or intervention from third parties, and the existence of legal remedies in the form of lawsuits, resistance, rebuttal submitted by the Respondent / debtor at the Court for reasons that are too low or Police Report. With regard to investor legal certainty, namely obtaining legal certainty and legal protection for the purchase of auction assets at the KPKNL in accordance with the provisions stipulated in article 14 of Law Number 25 of 2007 concerning Investment.Keywords : Utility Principle; Auction; Invesment Law.